COLLABORATIVE STRATEGIC READING VS RECIPROCAL TEACHING STRATEGY: EVALUATION STRATEGIES FOR IMPROVING INDONESIAN ELEMENTARY SCHOOL STUDENTS’ READING COMPREHENSION PERFORMANCE - Ni'matuzahroh, Ni'matuzahroh; Mangunsong, Frieda Maryam; Woei, Suen Mein; Karmiyati, Diah (Faculty of Psychology, Universitas Diponegoro, 2023)
Previous research has supported strategies of Collaborative Strategic Reading (CSR) and Reciprocal TeachingStrategy (RTS) to enhance reading comprehension performance in different populations but no study has beenfound to examine the effectiveness of both strategies of reading among elementary students. This study aims toinvestigate CSR and RTS among elementary students. A quasi-experiment with a non-randomized control grouppre-test-post-test design was used by 125 elementary school students and 3 teachers were equally assigned to theintervention and control group. Data collection used the intelligence test (CPM) and the reading comprehensiontest. Treatment was carried out over ten weeks with nine meetings for each treatment. Results showed that thereis a significant interaction effect between treatment and time, F(1, 36) = 140.27, p < .001, and a main effect oftime, F(1, 36) = 28.50, p < .001. However, there is no main effect of the treatment, F(1, 36) = 1.11, p = .299. Dueto the main effects of Time or Treatment, the post-test score (M = 18.32) is higher than the pretest ones (M =13.24), and the score of the RTS group (M = 13.95) is like one of the CSR groups (M = 12.53). It means thatchildren in the CSR group demonstrated significant improvement over than RTS group and the CSR was moreeffective than the RTS strategy. The RTS group (M = 13.95) is like the one of the CSR groups (M = 12.53, p < .05)and as expected the score of the CSR group (M = 19.89) is higher than that one of the RTS group (M = 16.7, p< .05). The CSR is a more effective method to improve reading comprehension performance for elementary schoolstudents than RTS.